Enhancing Industrial Occupational Safety through an IoT-based Monitoring and Access Management - Ugwechi Wejie-Okachi; Tamuno-Omie Joyce Alalibo; Emmanuel Chinweikpe Obuah (Research and Developments in Engineering Research Vol. 9, 2023)
This research focused on the successful deployment of an IoT-based monitoring and access control system for alcohol, fire and Liquefied Petroleum Gas (LPG) to significantly enhance workplace safety and hazard management within an industrial setting. The implementation of the industrial automation monitoring system was founded on the Internet of Things (IoT) paradigm. This system serves to bolster access control and safety management within the storage facility of a prominent industrial plant. The system surveys the environment for potential risks of LPG leakages and fire hazards. The system’s sensor modules, comprising alcohol, LPG, and fire sensors, capture relevant data which is then transmitted to microcontrollers for processing. The NodeMCU microcontroller plays a pivotal role in initiating the IoT-based alert mechanism. It accomplishes this by forwarding processed data to the ThingSpeak platform, SMS alerts, and the designated website accessible to authorised employees. The monitoring framework performs alcohol level checks on employees before granting them access to the facility. The system’s response is not limited to issuing alerts; it also triggers the activation of the fire suppression system through the sprinkler circuit. In real-time, the system swiftly disseminates alert and alarm notifications to critical stakeholders in the HSE department, fire office, security units, and other authorized personnel. This communication is facilitated through the industry’s dedicated website and a designated GSM line. By implementing this IoT-driven monitoring system, the industrial storage facility has effectively taken proactive measures to mitigate workplace hazards. This includes preventing the presence of intoxicated employees on-site, averting potential LPG leakages, and minimizing the risk of fire outbreaks.